Syariah based accounting (SbA): awareness of the accounting academicians in Malaysia - Abd Talib, Maswati; Abdullah, Amalina; Abdullah, Asna Atqa (Universiti Putra Malaysia Press, 2014)
Financial reporting based on Syari'ah is very important to ensure reliability and usefulness of information. The Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) has developed various accounting and auditing standards to ensure the quality of financial reports produced by institutions involved in Islamic products. The Malaysian Accounting Standards Board (MASB) has also taken the effort to come out with FRS-i-1, Presentation of Financial Statements of Islamic Financial Institutions (formerly known as MASB-i-1), to follow in the footsteps of AAOIFI. The education sector could take part in this caravan by updating the curriculum to incorporate the changes that are happening to better prepare the future workforce. However, very few institutions of higher learning in Malaysia offer Syari'ah-based Accounting (SbA) courses in their accounting programmes. The purpose of this study is to identify the level of awareness and knowledge of accounting academicians on SbA and to determine whether there is a need to offer SbA courses in institutions of higher learning so as to equip future accountants with SbA knowledge. Therefore, the objective of this study is to examine the level of awareness of SbA amongst accounting academicians and to understand reasons for higher learning institutions in Malaysia to offer SbA courses in their accounting programmes in the future. The respondents of this study were 40 accounting lecturers from selected Malaysian public institutions of higher learning. This study showed that there was a high degree of awareness among the academicians who agreed that SbA is needed to account for Islamic products and the majority agreed that SbA should be offered at institutions of higher learning. This study has several implications for society, government policies and education sectors. The academicians foresee the future needs of SbA in order to meet the demand in the Islamic Capital Market.